2018
DOI: 10.1111/ijfs.13774
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of ready‐to‐eat extruded nixtamalized maize‐based snacks enriched with grasshopper

Abstract: Summary The aim of this research was to prepare an extruded snack based on nixtamalized maize flour (Zea mays L.) (NMF) enriched with grasshopper meal (Sphenarium purpurascens Ch.) (GM) using a single screw extruder with a compression screw ratio of 3:1. A central experimental design comprising three independent variables, namely, extrusion temperature (T = 120–180 °C), feed moisture content (FMC = 18–22 g/100 g) and the grasshopper meal proportion (GMP = 0–40 g/100 g), was used. Increasing T decreased (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
7
30
1
Order By: Relevance
“…Another explanation for the lower ER is that the water reduced slip within the barrel, resulting in decreased torque; often the poor product expansion was due to insufficient pressure developed during extrusion (Hegazy, El‐Bedawey, Rahma, & Gaafar, ). This agreed with Vallée et al (), Cuj‐Laines et al () who reported that addition of back ear mushroom and grasshopper powder decreased ER of extrudes.…”
Section: Resultssupporting
confidence: 92%
“…Another explanation for the lower ER is that the water reduced slip within the barrel, resulting in decreased torque; often the poor product expansion was due to insufficient pressure developed during extrusion (Hegazy, El‐Bedawey, Rahma, & Gaafar, ). This agreed with Vallée et al (), Cuj‐Laines et al () who reported that addition of back ear mushroom and grasshopper powder decreased ER of extrudes.…”
Section: Resultssupporting
confidence: 92%
“…An increase in the SWP/CS proportion increased the H, probably due to the low feed moisture and low starch content with increasing SWP and PBP content, reducing the gelatinization of the starch, which ultimately resulted in a lower expansion; therefore, there was less water available for hydration of the starch granules that were not sufficiently plasticized with water and thus did not melt during extrusion, which led to an increase in the H values. The decrease in H with increasing ET can be attributed to the fact that the increase in temperature in the barrel decreases the viscosity of the mass required to produce a product of low density, which results in the formation of small bubbles with thin walls and the production of materials with the lowest H values (Cuj‐Laines et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Most snacks are made from raw materials rich in starch (corn, wheat, rice, oats, and potatoes). Corn starch provides all the features necessary for the production of highly acceptable extruded snacks (Cuj‐Laines et al, 2018). Snacks with increased nutritional content can be developed by the incorporation of legumes, vegetables, and fruits in the formulation (Pensamiento‐Niño et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Next, β‐glucan, pentosan, dietary fiber, vitamin E,, and hydration properties of traditional roasted Qingke and SE‐treated Qingke were compared and analyzed. As the material was subjected to the shear force of thermal processing, the denaturation of protein and the destruction of the crystal structure of starch would lead to a decrease in hydrophilic substances and increase in soluble substances (Cuj‐Laines et al., 2018). Compared with raw Qingke in Table 3, the WS of Qingke was significantly increased by SE treatment while there was no significant change at 50°C and significant decrease was observed at 37°C and 100°C in the roasted Qingke.…”
Section: Resultsmentioning
confidence: 99%